2023
DOI: 10.3389/fsurg.2023.1050172
|View full text |Cite
|
Sign up to set email alerts
|

Use of the superficial inferior epigastric vein in breast reconstruction with a deep inferior epigastric artery perforator flap

Abstract: BackgroundAutologous breast reconstruction is highly regarded in reconstructive surgery after mastectomy. DIEP flap reconstruction represents the gold standard for autologous breast reconstruction. The major advantages of DIEP flap reconstruction are its adequate volume, large vascular caliber and pedicle length. Despite reliable anatomy, there are procedures where the plastic surgeon's creativity is required, not only to shape the new breast, but also to overcome microsurgical challenges. An important tool in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Seven studies reported surgical take backs of which one was an RCT [ 31 ] and six retrospective non-randomised controlled cohort studies (Additional file 5 ) [ 31 , 35 , 38 , 42 , 55 , 57 , 58 ]. In the RCT [ 31 ] and the study with two consecutive series [ 58 ], there were considerable differences in takebacks between the groups, 13% vs. 55% and 1% vs. 10%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported surgical take backs of which one was an RCT [ 31 ] and six retrospective non-randomised controlled cohort studies (Additional file 5 ) [ 31 , 35 , 38 , 42 , 55 , 57 , 58 ]. In the RCT [ 31 ] and the study with two consecutive series [ 58 ], there were considerable differences in takebacks between the groups, 13% vs. 55% and 1% vs. 10%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… ? Varnava, 2023, Germany [ 57 ] Review of centres use of SIEV Case series (retrospective) P1: 150 DIEPs (107 pats) I1: 4 C: 146 NR NR O1. Complications O5.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, flap venous drainage may be improved in case of insufficient or inadequate outflow arising from the deep venous system alone. 23 The disadvantages of always preserving the SIEV may be prolonged operating times and the possibility of increased donor site complications, such as seroma. 24 Double-vein DIEP flap harvesting does not significantly increase the operative and ischemia times when compared with the single vein procedure.…”
Section: Discussionmentioning
confidence: 99%